NiH-catalysed proximal-selective hydroalkylation of unactivated alkenes and the ligand effects on regioselectivity - Wang, Xiao-Xu; Xu, Yuan-Tai; Zhang, Zhi-Lin; Lu, Xi; Fu, Yao (Nature communications, 2022)
Alkene hydrocarbonation reactions have been developed to supplement traditional electrophile-nucleophile cross-coupling reactions. The branch-selective hydroalkylation method applied to a broad range of unactivated alkenes remains challenging. Herein, we report a NiH-catalysed proximal-selective hydroalkylation of unactivated alkenes to access β- or γ-branched alkyl carboxylic acids and β-, γ- or δ-branched alkyl amines. A broad range of alkyl iodides and bromides with different functional groups can be installed with excellent regiocontrol and availability for site-selective late-stage functionalization of biorelevant molecules. Under modified reaction conditions with NiCl 2 (PPh 3 ) 2 as the catalyst, migratory hydroalkylation takes place to provide β- (rather than γ-) branched products. The keys to success are the use of aminoquinoline and picolinamide as suitable directing groups and combined experimental and computational studies of ligand effects on the regioselectivity and detailed reaction mechanisms. Difunctionalization of olefins is an ongoing and important focus of synthetic organic chemistry. Here the authors report a nickel-catalysed hydroalkylation of unactivated alkenes to obtain branched alkyl carboxylic acids or alkyl amines, using aminoquinoline and picolinamide as directing groups.